A cladistic analysis of the Scinax catharinae species group (Anura, Hylidae) - Calijorne Lourenço, Ana Carolina (2014)
The last ten years have witnessed important advances in our knowledge on the phylogenetic relationship among hylid frogs. Within this family‚ Scinax is one of the most species rich genera‚ having more than 100 species arranged in two clades: the S. catharinae and S. ruber clades. The monophyly of this genus is well supported in recent analyses‚ as well as its major clades. Currently two groups are known in the S. catharinae clade: the S. catharinae and S. perpusillus groups. The former has 32 known species‚ distributed from Argentina to Brazil‚ through Uruguay and Paraguay. The S. catharinae species group is recovered as monophyletic in recent analyses‚ however few species have so far been included. In this talk we present results of a phylogenetic analysis of the group. This analysis includes 26 of the 32 recognized species‚ plus several outgroups‚ and 98 phenotypic characters‚ and its results provide ample opportunity to discuss the evolution of several characters and biogeographic patterns.